Non-fatal acute barium carbonate poisoning following suicidal ingestion: A case report - Waiian Leong; Chunlian Li; Yuhui Long; Yanli Wang; Abraham KC Wai; Yi Huang; Feilung Lau (SAGE Open Medical Case Reports)
Acute barium poisoning is a rare but life-threatening method of suicide attempt, and it is a challenging disease in the emergency department. We report a case of barium carbonate poisoning in a 21-year-old man who ingested a large dose to attempt suicide and presented with gastrointestinal symptoms, gradual muscular weakness, and severe hypokalemia (K + 1.63 mmol/L). He was promptly managed with gastric lavage, respiratory support, and large doses of oral and intravenous potassium supplementation. In addition, intravenous sodium thiosulfate and continuous venovenous hemodiafiltration were administered to reduce the serum concentration of barium ions. Following comprehensive treatment, the patient recovered within 5 days and discharged home for 12 days. Clinicians should be vigilant when a patient presents gastrointestinal symptoms and limb weakness, associated with severe hypokalemia and cardiac arrhythmia over a short disease course as these may indicate potential barium poisoning. Furthermore, we advocate for paying more attention to the management of toxic substances and the mental health education of young adults.